Training the Students of the Department of Mathema- tics to Use Thinking Acceleration Paradigm (CAME) to Acquire Skills of Mathematical Communication - Obeid Dahwi, Hussein (Opción, 2019)
The aim of the research is to train the students of the mathematics department on the CAME model in the practical education program to enable them acquire the skills of mathematical communication. The study sample consisted of students of the fourth grade of the mathe- matics department at the College of Education for Pure Sciences / Universi- ty of Mosul for the academic year 2018-2019. The number of students was (62)studentswhoweredividedintotwogroups:thefirst wastrainedaccor- ding to the CAME model, (32, 30) male and female students, respectively. In order to achieve the objective of the research and test hypotheses, this requires the filling of a form of the skills of mathematical communication .The form was of (24) items that covered five area ( mathematical reading, writing, representation, listening, and discussion). The test was steadfast and honest After randomly dividing the sample of the research students into two research groups, a proposed training program was developed to train the experimental groups on the acceleration of thinking model, as well as deve- loping the objects schedule for the groups. The researcher applied his own experience to the groups on 15/10/2018, and the first course lased up to 10/ 1/2019, and then the sample students were sent to the secondary and high schools in the city of Mosul and its environs. There, the training tool was implemented through cooperation with the department teaching staff. After statistical data collection and analysis using T –Test for two independent samples, the results showed the following: - There is a statistically significant difference at (0.05) between the two avera- ges of mathematical communication achievement skills (mathematical reading, writing, representation, listening, discussion, and total) in the two experimental and control groups and in favor of the experimental group.